2023
DOI: 10.1088/1361-6595/ad01da
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a cusped helicon plasma thruster discharge

Pedro Jiménez,
Jiewei Zhou,
Jaume Navarro-Cavallé
et al.

Abstract: Experiments and simulations are used to analyze a compact helicon plasma thruster with a cusp in its internal magnetic field. The former rely on a compensated Langmuir probe and a Faraday cup, while the latter employ a hybrid PIC/fluid transport model combined with a frequency-domain electromagnetic field model. Measurements serve to tune the anomalous transport parameters of the model and overall show the same trends as the numerical results, including a secondary peak of electron temperature downstream in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The radial profile of plasma density is closely related to the magnetic field B 0 since the axial magnetic field will restrain the radial transport of electrons [33,34] which creates the helicon plasma by collisional ionization. Meanwhile, the radial profile of plasma density is significantly related to the power deposition determined by the profile of helicon wave fields with local electron kinetics [10,20,35].…”
Section: Plasma Morphology and Emission Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…The radial profile of plasma density is closely related to the magnetic field B 0 since the axial magnetic field will restrain the radial transport of electrons [33,34] which creates the helicon plasma by collisional ionization. Meanwhile, the radial profile of plasma density is significantly related to the power deposition determined by the profile of helicon wave fields with local electron kinetics [10,20,35].…”
Section: Plasma Morphology and Emission Spectrummentioning
confidence: 99%
“…Meanwhile, the radial profile of plasma density is significantly related to the power deposition determined by the profile of helicon wave fields with local electron kinetics [10,20,35]. Thus, the changed radial profile of plasma density might be related to the variations of plasma power deposition and the transport dynamics feature with the changed B 0 [10,33,34]. Noticeably, the radial integral of the plasma density in figure 7(b) seems unchanged, and this will be discussed in section 4.3.3.…”
Section: Plasma Morphology and Emission Spectrummentioning
confidence: 99%
“…It is found that the diamagnetic effect plays a significant role in the thruster generation. In addition, a hybrid PIC/fluid transport model combined with a frequency-domain electromagnetic field model was introduced by Jiménez [36] to analyze the helicon discharge with a cusped magnetic configuration in helicon thrusters. It is concluded that the cusp plays a central role in determining the plasma losses to the walls.…”
Section: Introductionmentioning
confidence: 99%
“…However, a considerable fraction of power is lost on plasma-wall recombination, excitation losses, and divergence losses. 13,14 Two main strategies for coupling the microwave power into the plasma have been explored, differing in the way MW is injected and propagated into the plasma chamber: the circular waveguide and the coaxial ECRTs. The first method consists of MW injected in the TE 11 (transverse electric) mode from a cylindrical waveguide through a dielectric window; the second method instead brings MW power through a coaxial cable and relies on the presence of an additional central conductor to obtain a TEM propagation mode.…”
Section: Introductionmentioning
confidence: 99%